Profiling gene expression dynamics underpinning conventional testing approaches to better inform pre-clinical evaluation of an age appropriate spironolactone formulation. (2nd January 2021) - Russell, Craig; Hussain, Majad; Huen, David; Rahman, Ayesha S.; Mohammed, Afzal R.
Abstract: There is a need to accelerate paediatric formulation evaluation and enhance quality of early stage data in drug development to alleviate the information pinch point present between formulation development and clinical evaluation. This present work reports application of DNA microarrays as a high throughput screening tool identifying markers for prediction of bioavailability and formulation driven physiological responses. With a focus on enhancing paediatric medicine provision, an oral liquid spironolactone suspension was formulated addressing a paediatric target product profile. Caco-2 cells cultured on transwell inserts were implemented in transport assays in vitro and DNA microarrays were used to examine gene expression modulation. Wistar rats were used to derive in vivo bioavailability data. In vitro, genomic, and in vivo data sets were concurrently evaluated linking drug transport and the genomic fingerprint generated by spironolactone formulation exposure. Significant changes in gene expression are reported as a result of formulation exposure. These include genes coding for ATP-binding cassette (ABC) transporters, solute carrier (SLC) transporters, cytochrome P450 (CYP) enzymes, and carboxylesterase enzymes. Genomic findings better inform pre-clinical understanding of pharmacokinetic and pharmacodynamic responses to spironolactone and its active metabolites than current in vitro drug transport assays alone.